RESENSI BUKU "BADRIYAH" - Artika, I Wayan - (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2016)
Judul Buku    : BadriyahPengarang    : Ayu WedaPenerbit       : Gambang Buku BudayaTahun Terbit   : Maret 2016Jumlah Halaman  : xiv + 207 halamanISBN    : 978-602-6776-15-0